Effect of low contents of a polyaniline derivative on the crystallization and electrical properties of blends with PVDF - Rocha, I. S.; Mattoso, L. H. C.; Malmonge, L. F. [UNESP]; Gregório Júnior, R. (Wiley-Blackwell, 1999)
The effect of low levels of poly(o-methoxyaniline) (POMA) on the crystallization, morphology, and electrical characteristics of blends with poly(vinylidene fluoride) (PVDF) were studied by infrared spectroscopy, AC electrical measurements, and optical microscopy. Undoped POMA has a strong effect in increasing the alpha-phase and decreasing the beta-phase content of PVDF in blends crystallized from solution. For blends melt crystallized, doped POMA promotes much greater homogeneity than undoped POMA. Interestingly, doped POMA promotes the nucleation and growth of unringed PVDF spherulites, whereas undoped POMA hinders it. The doping state of the POMA was also extremely important in determining the electrical behavior of the blend. (C) 1999 John Wiley & Sons, Inc.
Keywords: poly (vinylidene fluoride); polyanilines; blends; crystallization; morphology